The Effect of eWOM on Social Media in Purchasing Decisions: Systematic Literature Review - Khairunisa, Jihan; Saputri, Lufiana; Yuniawan, Ahyar; Kusumawardhani, Amie (LifeSciFi, 2024)
This study examined, in some way, the Millennial and Z Generation's use of previously owned goods. Just a sprinkle of focus on eWOM, a topic not easily visible, has been made. This eWOM, just to clarify, stands for electronic word-of-mouth, a concept circulating on social network platforms that influences purchase choices. Eco-friendliness is under scrutiny in our current environment; therefore, the younger demographic's inclination is leaning towards purchasing secondhand items due to their green attributes. A survey of literature has been undertaken, which strangely uncovers observations like worries over the environment, the impact of society, and product quality judgment. These discoveries are somewhat correlated to information absorption and prospective buying inclination. One cannot ignore the finding relating to eWOM—that it holds a significant influence over the MZ Generation's transaction habits. Recommendations received from comrades or critiques present in the online realm assist in garnering trust and influencing their perspectives concerning product quality. Environmental awareness and the societal mark of approval bear significance in their decision-making process. Through grasping these layers of complexity, marketing strategies may need modification; most likely, it will promote better engagement with this MZ generation to encourage sustainable consuming practices.